Homo temporalis : German Jewish thinkers on time - Lebovic, Nitzan, 1970- (Signale (Ithaca, N.Y.), 2024)
"A group of modern Jewish intellectuals grappled with concepts of time and temporality. Martin Buber, Walter Benjamin, Hannah Arendt, and Paul Celan stand at the center of our contemporary understanding of religion, critical theory, politics, and literature. All four rejected notions of borders, territory, or national origin. Their path teaches us about three 'temporal turns'-in 1900, in 1945, and in 2000."--